Managerial Ownership Moderates the Effects of Earnings Management, Capital Structure, and Business Risk on Financial Performance - Puspita Sari Widiyanti; Iin Rosini; Nofryanti Nofryanti (Sean Institute, 2026)
This study examines whether managerial ownership moderates the effects of earnings management, capital structure, and business risk on the financial performance of Indonesian mining firms, an industry characterized by high volatility due to commodity-price cycles and regulatory dynamics. The objective is to clarify inconsistent prior evidence by testing both direct effects and moderation using a value-based performance measure. Employing a quantitative causal design, the study uses secondary data from audited annual financial statements of mining companies listed on the Indonesia Stock Exchange. Purposive sampling yields 14 firms observed over a five-year period, producing 70 firm-year observations. Financial performance is proxied by Economic Value Added (EVA), while earnings management, capital structure, business risk, and managerial ownership are operationalized using standard accounting-based proxies. Panel data regression is conducted using EViews to estimate the main effects and interaction terms. The results show that earnings management does not significantly affect EVA, whereas capital structure and business risk have positive and significant effects on EVA. However, managerial ownership does not moderate the relationships between earnings management, capital structure, or business risk and financial performance. These findings suggest that, in the mining sector, value creation is more closely linked to financing structure and risk-handling capacity than to earnings-smoothing behavior, and that low managerial ownership may limit its governance role as a moderating mechanism.